IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) CONCERNING ADVANTAGE ALLOCATIONS TO IMPROVE COMPANY REPUTATION IN PT PUPUK KUJANG CIKAMPEK - Sungkono; Isyanto, Puji; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine, analyze and explain the Implementation of Corporate Social Responsibility as part of the company’s profit allocation to improve the company’s reputation at PT Pupuk Kujang Cikampek. This research is expected to be able to contribute to the development of science in management science with the application of the implementation of corporate social responsibility to the community. This research is a qualitative descriptive study with case study method through in-depth interviews about the Implementation of Corporate Social Responsibility at PT Pupuk Kujang Cikampek, with informants or key informants consisting of management, beneficiaries, coaches, distributors, and experts . The results of the study conducted by interviews, then analyzed with standard deviations obtained several criteria that the implementation of CSR about the allocation of benefits criteria is good (S = 0.7173 - 0, 8846); Based on research by conducting interviews with very good criteria for the implementation of CSR, have seen indications of the importance of "policy" as an important part of the implementation of CSR through distribution of part of the company’s profits that have been implemented by PT Pupuk Kujang Cikampek. This is supported by the results of the SWOT analysis with the highest IFAS value of = 0.668. So it can be concluded that in addition to Triple Buttom Line as the basic concept of CSR (Profit, People, and Planet), the company’s management policy is the base practice of the company’s strategy to enhance reputation.